Retraction notice to "MicroRNA-19a and -19b regulate cervical carcinoma cell proliferation and invasion by targeting CUL5" [Canc. Lett. 322 (2012) 148–158]. (1st October 2021) - Xu, Xue-Mei; Wang, Xiao-Bo; Chen, Miao-Miao; Liu, Tao; Li, Yi-Xuan; Jia, Wei-Hua; Liu, Min; Li, Xin; Tang, Hua
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. Upon investigation, it was discovered that 4 out of 8 images contain fabrication. Fig. 6D, E, 8E and 7F have used the same microscopic image for different experimental settings. The Figure represented in 8E is the correct image placement. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.